(untitled) (AYUSHDHARA, 2016)
Various reports suggest that 30 to 50% of women in the reproductive age group suffer from excessive and irregular uterine bleeding by various causative factors. Various treatments prescribed in modern medicine like hormone therapy, antiprostaglandins and antifibrinolytic agents etc have not proved their definite efficacy inspite of high price and side effect, and lastly hysterectomy may lead to hormonal imbalance and psychological upset in young fertile women. Ayurveda considered the same as Asrigdara and Stambhana Chikitsa is the commonly prescribed management for this. But prior to Stambhana Chikitsa, Pachana Chikitsa is to be performed as without Amapachana, Stambhana Chikitsamay not show better efficacy. So a clinical trial was conducted on 30 Patients, who were divided in 2 groups, 15 patients in each. In Group A (Control group) Stambhana Chikitsa alone with Panchavalkala Kashaya was given and in Group B (Trial group) Stambhana Chikitsawith Panchavalkala Kashaya proceeded by Pachana Chikitsa with Guduchyadi Kashaya was given to patients for treatment. The present Study reveals, significant benefit in trial group to reduce symptoms of Asrigdara with a p-value of <0.001 in comparison with alone Stambhana Chikitsa.